Evaluating Of Call Stock Options In The Kuwait Stock Exchange - Bentouir, Naima; Bendob, Ali; Benzemra, Mankour (University of Eloued جامعة الوادي, 2018)
The options pricing on financial assets represents a subject of great interest to academics and practitioners in the financial markets and a phenomenon that has occupied specialists in the financial domain and mathematics. The Black-Sholes model (1973) is the benchmark model of many models which provides us with a basic tool for the pricing option contracts traded in markets, this model was built on many assumptions which are the stability of volatility and the risk-free rate and the normal distribution. The main objective of this study is the exhibition and interpretation methods that relate to the assessment and pricing of options on financial stocks market, through the comparison between the theoretical options prices under Black-Scholes model, Monte Carlo Simulation method and the current option prices on market, and testing the validity of the both models on predicting the market prices, by an empirical study for the period of 26 December 2013 to 08 May 2014, with daily data using R software and its packages. It was found that the Black-Sholes model is not perform when the volatility is higher in the both of periods 6 and 9 months, but for the period of one year the B-S model proved it ability to predict the current prices with a positive relationship, other finding highlighted the outperformance of the Monte Carlo Simulation Method to predicting current price when the volatility is lower only on both periods 6 and 9 months.
مجلة رؤى المجلد الثامن العدد الأول
Keywords: Pricing options, Black-Scholes model, option market, Call option, Kuwait stock exchange, Monte Carlo Simulation, Regression analysis. Jel Classification Codes : C13, C15, G12, G13, G15, G17.